EVIDENCE REQUIREMENTS FOR REIMBURSEMENT OF PHARMACEUTICALS ACROSS EUROPE - Oyebode, Oyinlola; Garrett, Zoe; George, Elizabeth; Cangini, Agnese; Muscolo, Luisa Anna Adele; Warren, Simone; Nemeth, Bertalan; Földesi, Csenge; Heislerová, Marcela; Gajdošová, Eva (International journal of technology assessment in health care, 2015)
OBJECTIVES: The objective of this study was to compare evidence requirements for health technology assessment of pharmaceuticals by national agencies across Europe responsible for reimbursement decisions focusing specifically on relative effectiveness assessment. METHODS: Evidence requirements from thirty-three European countries were requested and twenty-nine national agencies provided documents to review. Data were extracted from national documents (manufacturer's submission templates and associated guidance) into a purpose-made framework with categories covering information about the health condition, the technology, clinical effectiveness and safety. RESULTS: The level of detail in the required evidence varies considerably across countries. Some countries include specific questions while others request information under general headings. Some countries include all information in a single document, which may or may not include guidance on how to complete the template. Others have specific guidance documents or methods and process manuals that help with the completion of the submission templates. Despite differences in quantity and detail, the content of the evidence requirements is broadly similar. All countries ask for information on the health technology, target disease, and clinical effectiveness and safety. However, one country only requests clinical effectiveness information as part of cost-effectiveness analyses. We found twenty-six evidence requirements for which generic answers may apply across borders and nineteen in which countries requested nationally specific information. CONCLUSIONS: This work suggests that it would be possible to put together a minimum set of evidence requirements for HTA to support reimbursement decisions across Europe which could facilitate collaboration between jurisdictions.
Keywords: Prescription Drugs; hodnocení biomedicínských technologií; Technology assessment; lidé; Europe; Technology Assessment, Biomedical; Delivery of health care; Evropa; léky na předpis; analýza nákladů a výnosů; Health policy; biomedical; Biomedical technology; Reimbursement mechanisms; Cost-Benefit Analysis; Humans